Anisotropic Metal Chalcogenide Nanomaterials Synthesis, Assembly, and Applications - Moon, Geon Dae (SpringerBriefs in Materials,, 2019)
This book explores the recent advances in designing and synthesizing one- and two-dimensional metal chalcogenide nanostructures, along with their practical applications, helping readers understand what has happened, and what is currently happening in the field of nanotechnology. It also includes a comprehensive table showing 1D and 2D nanostructured metal chalcogenides, which presents the recent developments from a synthetic point of view. Further, it describes the wide applicability of anisotropic metal chalcogenides, such as in electronics, energy storage and conversion, and sensors. Lastly it discusses the current understanding of the thermodynamic and kinetic aspects associated with the forming mechanisms of anisotropic metal chalcogenide nanostructures. This book is a valuable reference resource for practitioners and researchers, enabling them to obtain a quick overview of anisotropic metal chalcogenide nanomaterials through synthetic approachesand related applications. Presenting representative applications of anisotropic metal chalcogenide nanomaterials that are important in the industrial sector, it is also of interest to academics and industry specialists.